Organic–inorganic composite materials as photoinitiator for controlling/living polymerization. Issue 3 (11th September 2015) - Liang, En Xiang; Lu, Mang; Hou, Zhao Hui; Huang, Yan; He, Bin Hong; Wang, Guo Xiang; Liu, Li Chao; Wu, Hu; Zhong, Ming
ABSTRACT Titanium dioxide (TiO2)/graphitic carbon nitride (g‐C3N4) composites were first used as photoinitiator for photochemically mediated controlled/living polymerization of methyl methacrylate. The polymerization was successfully carried out in polyethylene glycol at room temperature with FeCl3·6H2O/N, N, N ′, N ′, N ″‐pentamethyldiethylenetriamine as complex catalyst and ethyl 2‐bromoisobutyrate as initiator in this case. A pseudo‐first‐order dependence of the monomer concentration on the polymerization time was observed. TiO2/g‐C3N4 was verified to be an efficient photoinitiator. The polymerization was controlled to produce poly(methyl methacrylate) with narrow molecular weight distribution and controlled number average molecular weight (Mn, GPC). The Mn, GPC matched well with the theoretical values when using both UV and sunlight irradiation as light source. The effects of reaction conditions on the polymerization were investigated. The polymerization could be started and stopped through periodically switching on/off the light. The living nature was further supported by the chain extension experiments. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42891.